2023
DOI: 10.1177/09731296221145066
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Phytochemical Profiling (GC-MS and HPLC) and Evaluation of Antioxidant Activities of Wild, in Vitro Cultured and Greenhouse Plants of Kaempferia grandifolia Saensouk and Jenjitt and Kaempferia siamensis Sirirugsa; Rare Plant Species in Thailand

Abstract: Background Kaempferia grandifolia and Kaempferia siamensis are rare plant species in Thailand used for medicinal, food, and ornamental purposes. Objectives To compare the phytochemical profiles of leaf and rhizome extracts from wild, in vitro culture, and greenhouse plants of K. grandifolia and K. siamensis. Materials and Methods Leaf and rhizome were extracted and analyzed phytochemically by high-performance liquid chromatography (HPLC), gas chromatography mass spectrometry (GC-MS), total phenolic contents (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Our results were contrary to Yeap et al (2017) who reported boesenboxide, crotepoxide, 2ˊ-hydroxy-4,4ˊ,6ˊ-trimethoxychalcone, kaempfolienol and zeylenol in the rhizome of K. angustifolia from Java, Indonesia using liquid chromatography-mass spectrometry (LC-MS), while Tang et al (2014) also reported 8 phytochemical compounds;kaempfolienol, crotepoxide, boesenboxide, 2'-hydroxy-4,4',6'-trimethoxychalcone, zeylenol, 6-methylzeylenol, (24S)-24-methyl-5lanosta-9(11), 25-dien-3 -ol and sucrose, -sitosterol, and its glycoside in the rhizome of K. angustifolia from Java, Indonesia using mass spectrometry (MS). Nonthalee et al (2023) used comparative phytochemical profiling (GC-MS and HPLC) to evaluate the antioxidant activities of wild, in vitro cultured, and greenhouse plants of Kaempferia grandifolia and Kaempferia siamensis from Thailand. Their GC-MS results revealed 38 compounds in K. grandifolia and 19 compounds in K. siamensis.…”
Section: Discussion Discussion Discussionmentioning
confidence: 99%
“…Our results were contrary to Yeap et al (2017) who reported boesenboxide, crotepoxide, 2ˊ-hydroxy-4,4ˊ,6ˊ-trimethoxychalcone, kaempfolienol and zeylenol in the rhizome of K. angustifolia from Java, Indonesia using liquid chromatography-mass spectrometry (LC-MS), while Tang et al (2014) also reported 8 phytochemical compounds;kaempfolienol, crotepoxide, boesenboxide, 2'-hydroxy-4,4',6'-trimethoxychalcone, zeylenol, 6-methylzeylenol, (24S)-24-methyl-5lanosta-9(11), 25-dien-3 -ol and sucrose, -sitosterol, and its glycoside in the rhizome of K. angustifolia from Java, Indonesia using mass spectrometry (MS). Nonthalee et al (2023) used comparative phytochemical profiling (GC-MS and HPLC) to evaluate the antioxidant activities of wild, in vitro cultured, and greenhouse plants of Kaempferia grandifolia and Kaempferia siamensis from Thailand. Their GC-MS results revealed 38 compounds in K. grandifolia and 19 compounds in K. siamensis.…”
Section: Discussion Discussion Discussionmentioning
confidence: 99%